Maraval Waterworks. - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
A wooden gangway leads to the reservoir which is located at the foot of some lush mountains. Buildings with steep-pitched roofs also dot the same compound.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Maraval; Reservoirs--Trinidad and Tobago; Architecture--Trinidad and Tobago; Pavilions--Trinidad and Tobago; Footbridges--Trinidad and Tobago